PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS MODEL PEMBELAJARAN WE-ARe (Warm-Up, Exploring, Argumentation, Resume) DALAM MEMFASILITASI PENINGKATAN HASIL BELAJAR KOGNITIF SISWA KELAS XI SMA NEGERI 6 KOTA TERNATE - Amin, Astuti Muh; Ainurhayati, Ainurhayati; Muna, Lintal (Biosel Biology Science and Education, 2023)
The objectives of this research include (1) determining the validity of worksheets based on the WE-ARe learning model for class XI students at SMA Negeri 6 Ternate City and (2) determining the effectiveness of worksheets based on the WE-ARe learning model in facilitating increased cognitive learning outcomes for class XI students at SMA Negeri 6 Ternate City. This research is development research with a research design adopting the Thiagarajan 4-D development model. The 4-D development model consists of defining, designing, developing, and disseminating. The results of the research show (1) the validity of worksheets based on the WE-ARe learning model was obtained on average in the very valid category; (2) LKS based on the WE-ARe learning model effectively facilitate the improvement of cognitive learning outcomes for class XI students at SMAN 6 Ternate City. The t test shows a sig (2-tailed) value of 0.003 0.05, so Hi is accepted and Ho is rejected. The conclusion of the research is that the use of student worksheets (LKS) based on learning models (WE-ARe) warm-up, exploration, argumentation, resumes can facilitate increased cognitive learning outcomes for class XI students at SMA Negeri 6 Ternate City.